2007
DOI: 10.3201/eid1307.060740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internal Border Control on Spread of Pandemic Influenza

Abstract: Population size, travel rates, and residence of travelers can aid in determining travel restrictions as a control policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…This included three that specifically evaluated the effect of air travel restrictions in mitigating a pandemic. They observed that unless air travel restrictions were imposed in approximately 100% of the affected countries, there would be no effect on influenza spread, although these measures delayed the peak of the influenza epidemic to varying degrees (Cooper et al., 2006; Hollingsworth et al., 2006; Wood et al., 2007). One article studied the effect of travel restriction between neighbouring communities during a pandemic with similar results (Nigmatulina and Larson, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This included three that specifically evaluated the effect of air travel restrictions in mitigating a pandemic. They observed that unless air travel restrictions were imposed in approximately 100% of the affected countries, there would be no effect on influenza spread, although these measures delayed the peak of the influenza epidemic to varying degrees (Cooper et al., 2006; Hollingsworth et al., 2006; Wood et al., 2007). One article studied the effect of travel restriction between neighbouring communities during a pandemic with similar results (Nigmatulina and Larson, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…During the 2009 H1N1 pandemic, countries including China, Japan, Hong Kong, Singapore, and Australia implemented various border control strategies to prevent arriving airline passengers from infecting the countries' citizens [32], [33], [34], [35]. Health authorities screened arriving passengers for flu-like symptoms using thermal scanners.…”
Section: Discussionmentioning
confidence: 99%
“…These screenings will miss asymptomatic individuals [35], and in particular infected individuals with no fever. However border control has been shown to delay the local community transmission [32], [33], [34], which may allow sufficient time for health interventions, such as vaccinations. On the other hand, border control may only delay transmission and could still result in a second wave, as seen in the simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the full extent to which border control measures actually contribute to realworld epidemic preventions is still rather unknown. While some reports [33][34][35][36] provided rather pessimistic estimations on the effectiveness of border control, recent evaluations of the entry screening policies adopted by different nations during the 2009 H1N1 pandemic [37] demonstrated that long-range travel control significantly delayed disease transmission, relative to countries which did not employ a strategy for screening of incoming passengers. Due to such conflicting reports, more studies on the relevance of border control measures are needed.…”
Section: Entry Screening Of Long-range Travelersmentioning
confidence: 99%